Spatial segregation and migration in the city of Athens: Investigating the evolution of urban socio‐spatial immigrant structures - Panori, Anastasia; Psycharis, Yannis; Ballas, Dimitris (Population space and place, 2019)
Migration has long had an impact on spatial segregation within the metropolitan area of Athens. This process has also been affected by local economic restructuring mechanisms, which, in recent years, have evolved within the context of the 2008 economic crisis. This study attempts to shed light on the evolution of the spatial segregation of immigrants within the metropolitan area of Athens, during a period of a rapid urban transformation, using data from the last two census waves (2001 and 2011). Given that previous evidence indicates both vertical segregation in the immigrant labour market structure and diffused immigrant settlements, the work presented here investigates the ways in which urban migrant structures have evolved through local economic restructuring processes, as well as throughout space. The study presents a set of quantitative urban segregation indicators, covering the aspects of evenness, exposure, concentration, and centralisation. It also captures the most significant occupational changes between different migrant‐status groups (non‐EU and EU immigrants), during a crucial period for Athens. Evidence indicates that there has been an overall raise in immigrant settlement segregation, accompanied by an increased centralisation trend. Moreover, the urban transformation through economic restructuring that took place in Athens, following the general EU trend towards a knowledge‐based economic model, has altered the immigrant labour market structure, leading to vertical segregation patterns, driven by professionalisation.